Elections and Policies: Evidence from the Covid Pandemic - Daryna Grechyna (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the evolution of public policies before the scheduled political elections based on the government responses to the Covid pandemic. The results of an event study in a sample of countries that experienced political elections during the first year of the pandemic suggest that "lockdown style" policies were more stringent the further away countries were from election dates. The gradual relaxation of "lockdown style" restrictions ahead of the elections was driven by policies in low income, less democratic countries, and countries with relatively low social trust. Covid-related "economic support" policies were not significantly affected by the scheduled political elections. Placebo tests based on a random sample of countries that did not experience political elections in the first year of the pandemic confirm the validity of the results.
Keywords: D72; C23; O57; 330; political cycles; event study; Covid pandemic